ANALISIS SIFAT FISIKO KIMIA NUGGET RAJUNGAN (PORTUNUSPELAGICUS) DENGAN BERBAGAI JENIS TEPUNG SEBAGAI BAHAN PENGISI - Rezky Awaliah; Subari Yanto; Andi Sukainah (Universitas Negeri Makassar, 2017)
This study aimed to determine the effect of powderkind and concentration powder of the physical and chemical characteristics of crab nugget. This research was conducted in two stage. The first stage is hedonic test crab nuggets with three kinds powder that is: sago flour, cornmeal, and wheat flour. The second stage of analysis of the protein and ash content. This research used a completely randomized design factorial. The result of the research showed that the best crab nuggets of sago flour with 2% concentration, with nutrition content: protein content were 31,29% and ash content were 5,31%.